Electrodeposited Manganese Oxide based Redox Mediator Driven 2.2 V High Energy Density Aqueous Supercapacitor. (15th March 2022) - Pappu, Samhita; Rao, Tata N.; Martha, Surendra K.; Bulusu, Sarada V.
Abstract: Aqueous supercapacitors with enhanced energy densities are much needed for their non-toxic and environmental benignity. Metal oxide based pseudocapacitors enhance the specific capacitance and energy density of the device by enlarging the potential window of aqueous electrolyte beyond 1.0 V along with faradaic participation. To capture this advantage, MnO2 nanosheets are synthesized by eco-friendly electrodeposition technique. The charge storage capability of MnO2 in 0.5 M Na2 SO4 could be extended to 1.20 V vs. Ag/AgCl, thus becoming the best positive electrode for asymmetric supercapacitors (ASCs). The effect of potassium iodide (KI) redox additive to the electrolyte in improving the energy density and device performance is analyzed with varying concentrations. ASC designed with YP-50 carbon and MnO2 as negative and positive electrodes in optimized KI concentration with 2.2 V electrochemical window resulted in superior specific capacitance of 134 F g −1 and capacity retention of 83% for 10, 000 cycles with a high energy density of 90 Wh kg −1 owing to the dual pseudocapacitance of active material and electrolyte. The work further provides an understanding of MnO2 charge storage properties beyond the most reported 0–0.8/0–1.0 V potential window and redox mediator's role in boosting overall device performance in aqueous ASC's. Graphical abstract: Image 1 Highlights: Synthesis of binder free MnO2 by DC and pulse modes of electrodeposition. Redox additive in electrolyte enhancing the asymmetric device characteristics. 134 F g −1 at 3 A g −1 specific capacitance and 90 Wh kg −1 energy density. Promising application by 40 LED's and fan demonstration.